EFFECT OF ENVIRONMENTAL PERFORMANCE AND BOARD OF COMMISSIONERS ON ENVIRONMENTAL DISCLOSURES - Erlangga Suryarahman; Huda Trihatmoko (Universitas PGRI Madiun, 2021)
ABSTRACT This study aims to obtain empirical evidence about the influence of environmental performance, board size of commissioners, independent commissioners, and the board of commissioners meetings on environmental disclosure. The sample of this study was 81 mining companies participating in PROPER which were listed on the Indonesia Stock Exchange during the 2014-2018 period. Environmental disclosure was assessed with GRI-4 guidelines and data were analyzed using multiple linear regression analysis. The results of this study indicate that environmental performance and independent commissioners have no effect on environmental disclosure, on the other hand, the board size of commissioners and the board of commissioners meeting have an effect on environmental disclosure. ABSTRAK Penelitian ini bertujuan untuk memperoleh bukti secara empiris mengenai pengaruh kinerja lingkungan, ukuran dewan komisaris, komisaris independen dan rapat dewan komisaris terhadap pengungkapan lingkungan. Sampel penelitian ini sebanyak 81 perusahaan pertambangan peserta PROPER yang terdaftar di Bursa Efek Indonesia selama periode 2014-2018. Pengungkapan lingkungan dinilai dengan pedoman GRI-4 dan data dianalisis menggunakan analisis regresi linier berganda. Hasil dari penelitian ini menunjukkan bahwa kinerja lingkungan dan komisaris independen tidak berpengaruh terhadap pengungkapan lingkungan, disisi lain ukuran dewan komisaris dan rapat dewan komisaris berpengaruh terhadap pengungkapan lingkungan.